Determination of the Optimal Conditions of t he Bond of Nickel ( II) Ion Complex with Dimethyl glyoxime Reagent - S.B.Ubaydullaeva; U.X. Sodikov (Genius Journals, 2022)
This paper describes experimental methods for the separation of nickel ions from the adsorbent using dimethylglyoxime in the regeneration of adsorbents.A universal buffer solution with pH = 8.0 was used to study the dependence of the composition of buffer solutions on the main reaction Ni2+-Rreagent) components
Keywords: Ni (II) ions; spent MDEA solution; Chugaev's reagent; pH value